(untitled) (International Journal of Engineering Sciences & Management Research, 2015)
Medical jurisprudence is nothing but a medicine Science which opens all gateways to a healthy life and increases the longevity of one’s life. In other words, it is worthy to state that Medical Science deals with very serious aspects of human life, and hence negligence is a very grave word in the dictionary of Medical Science. As per the law, the liability of a doctor for medical negligence shall be civil or criminal or both, Where in a civil liability i.e., torturous liability, an aggrieved person or entity can claim damages in a court. But, in the case of a criminal liability, there is a problem, since it is very difficult to trace out mens rea (mental elements) along with actus rea which are the important ingredients of a criminal liability. And thus, it means a civil liability is the sole legal system for resolving the problem of medical negligence, where the sufferer will only receive damages that may not always suffice the costs or losses/damages incurred by medical negligence.